Managing uncertainties in the implementation of Gaza Phoenix recovery framework - Barbanente, Angela; Khakee, Abdul (Plurimondi, 2025)
The paper proposes a model for the implementation of reconstruction projects in the Gaza region as outlined in the Gaza Phoenix Recovery Framework. The model includes creating alternative scenarios and mapping uncertainties against the backdrop of these scenarios adopting a participatory approach, which is consistent with a fundamental principle underlying the GPRF. The paper outlines operational guidelines for preparing scenarios and assessing uncertainties, assigning the GPRF multidisciplinary team the role to facilitate, give voice to and support the population's perspective on the reconstruction of the Gaza region.